Inter-rater reliability of ratings on the six-item Positive and Negative Syndrome Scale (PANSS-6) obtained using the Simplified Negative and Positive Symptoms Interview (SNAPSI). (18th August 2018) - Kølbæk, Pernille; Blicher, Anne B.; Buus, Chanette W.; Feller, Sandra G.; Holm, Tine; Dines, David; O'Leary, Kathrine M.; Sørensen, Rune S.; Opler, Mark; Correll, Christoph U.; Mors, Ole; Bech, Per; et al.
Abstract: Purpose: The six-item version of the Positive And Negative Syndrome Scale (PANSS-6) is a brief rating scale focusing on core symptoms of schizophrenia. In order to facilitate rating of PANSS-6 and selected items from other common psychiatric rating scales, we recently developed the Simplified Negative and Positive Symptoms Interview (SNAPSI). The objective of the present study was to test the inter-rater reliability of PANSS-6 ratings obtained using the SNAPSI. Materials and methods: Using the SNAPSI, seven raters (psychiatrists, first-year psychiatry residents and psychologists) performed a total of 56 PANSS-6 ratings of 12 in- or outpatients with schizophrenia. As a measure of inter-rater reliability, we calculated the intra-class correlation coefficient (ICC, ≥0.75 = excellent, 0.40–0.74 = fair to good, <0.40 = poor) for the PANSS-6 total score and individual item scores. Furthermore, for the PANSS-6 total scores obtained by the six noncertified PANSS raters, we calculated the median deviation from the PANSS-6 total scores obtained by the only certified PANSS rater. Results: The ICC for the PANSS-6 total score was 0.74 ( F  = 2.84, p  = .03). The ICCs for the six individual PANSS-6 items ranged from 0.45 (N6 – Lack of spontaneity & flow of conversation) to 0.76 (P3 – Hallucinatory behavior). The PANSS-6 total scores obtained by the six noncertified PANSS raters deviated by a median of 12.7% (interquartile range: 6.2–20.0) from the PANSS-6 total scores obtained by the certified PANSS rater. Conclusions: We found a good level of inter-rater reliability of PANSS-6 ratings obtained using the SNAPSI for seven raters with varying levels of clinical and research experience.